Mobile app for audience interaction & engagement - Loy, Annis Boon Yin (2019)
Smartphones have played an important role in helping people become more connected with each other and more effective in solving day-to-day problems. These devices have been increasingly popular and more integrated in people’s lives as people use it more than just for communication. There are tons of mobile applications available on the app store, ranging from entertainment to productivity apps, to engage the users. However, apps developed to interact and engage audience are limited. This project aims to create a mobile app which interacts and engages attendees at an exhibition or trade show event. The features in the mobile app include an interactive feed, limited time deals and information about the event. User friendly features are also incorporated for users for better overall user experience with the app. For this project, an Android app and a web application is developed. Android was chosen due to the majority of smartphone users using the Android operating system. The web application serves as a platform for easier upload of content into the mobile application. The mobile application is developed in Android Studio (IDE) with Android SDK while the web application is created using XAMPP framework. MySQL and Firebase real-time database are utilised for the data storage of this project. Debugging and functional testing were conducted to ensure that both the mobile and web app are optimised and less prone to bugs and defects. The results of the testing also make sure that the features in the app are well-functional and meets the requirements of the end user. Overall, the objectives of the project were successfully met on time. However, there is always room for improvement and potential future enhancements for the app.